2011
DOI: 10.4174/jkss.2011.81.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of adipose tissue-derived stem cells for liver failure according to the transplantation routes

Abstract: PurposeEven though adipose tissue-derived stem cells (ADSCs) have been spotlighted as a possible alternative for liver transplantation in an experimental setting, the mechanism by which ADSCs improve liver dysfunction remains poorly characterized. The objective of this study was to evaluate the therapeutic ability of undifferentiated ADSCs, and find a few clues on how ADSCs alleviate liver damage by comparing the transplantation routes.MethodsIn vitro generated human ADSCs were checked for surface markers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 29 publications
2
33
0
3
Order By: Relevance
“…As shown in Table 1, allogeneic umbilical tissue-derived MSCs have also improved MELD scores and serum levels of albumin and bilirubin. Moreover, as shown in Table 2, human MSCs have been safely administered in rodents, also exhibiting some therapeutic effects, thereby supporting the low immunogenicity of MSCs [84][85][86][87][88].…”
Section: Mscsmentioning
confidence: 84%
“…As shown in Table 1, allogeneic umbilical tissue-derived MSCs have also improved MELD scores and serum levels of albumin and bilirubin. Moreover, as shown in Table 2, human MSCs have been safely administered in rodents, also exhibiting some therapeutic effects, thereby supporting the low immunogenicity of MSCs [84][85][86][87][88].…”
Section: Mscsmentioning
confidence: 84%
“…The application of bone marrow MSC transplantation for ALF has been a research hotspot over recent years (19). …”
Section: Discussionmentioning
confidence: 99%
“…Similar to hUC-MSCs treatment, mUC-MSCs transplantation significantly increases the survival rate in acute hepatic failure mice [55]. Although several studies have indicated that the hepatogenic differentiation potential of MSCs contributes in rescuing mice with acute hepatic failure [5658], it is generally agreed that the therapeutic effects of MSCs in attenuating liver injury appear to result from trophic support [55,59,60]. Interestingly, semi-quantitative RT-PCR revealed that cultured mUC-MSCs express mRNA of VEGF, FGF2, Ang2, PDGFβ, IL-6, SCF, Cxcl12, TGFβ, iNOS, and GDNF, but not IL-10, HGF, and BDNF, which are expressed by human MSCs [33,59,6164] (Table S4).…”
Section: Discussionmentioning
confidence: 99%